Involvement of PKMζ in Stress Response and Depression - Liu, Jianfeng (Frontiers in Cellular Neuroscience, 2022)
The stress system in the brain plays a pivotal role in keeping humans and animals from harmful stimuli. However, excessive stress will cause maladaptive changes to the stress system and lead to depression. Despite the high prevalence of depression, the treatment remains limited. PKMζ, an atypical PKC isoform, has been demonstrated to play a crucial role in maintaining long-term potentiation and memory. Recent evidence shows that PKMζ is also involved in stress response and depressive-like behavior. In particular, it was demonstrated that stress that resulted in depressive-like behavior could decrease the expression of PKMζ in the prefrontal cortex, which could be reversed by antidepressants. Importantly, modulation of PKMζ expression could regulate depressive-like behaviors and the actions of antidepressants. These data suggested that PKMζ could be a molecular target for developing novel antidepressants. Here, I review the advance on the role of PKMζ in mediating stress response and its involvement in the development of depression.